5-(Adamantan-1-yl)-3-[(4-benzylpiperazin-1-yl)methyl]-1,3,4-oxadiazole-2(3 H )-thione - El-Emam, Ali A.; El-Brollosy, Nasser R.; Attia, Mohamed I.; Said-Abdelbaky, Mohammed; García-Granda, Santiago (Acta Crystallographica Section E: Structure Reports Online, 2012)
The molecule of the title compound, C24H32N4OS, is a functionalized 1,3,4-oxadiazole-2-thione with substituted piperazine and adamantanyl substituents attached at the 3- and 5-positions, respectively, of the oxadiazole spacer with an approximately C-shaped conformation. In the crystal, molecules form dimers via C—H⋯S interaction. The piperazine ring has a chair conformation; the substituents S, methylene C and adamantane C of the essentially planar oxadiazole ring are approximately in the same plane, with distances of −0.046 (2), −0.085 (5) and 0.003 (4) Å, respectively. The dihedral angle between the planes of the phenyl and oxadiazole rings is 31.3 (3)°.